Novel therapeutic approaches to simultaneously target rhinovirus infection and asthma/COPD pathogenesis [version 1; referees: 2 approved] - Carmen Mirabelli; Els Scheers; Johan Neyts (F1000Research, 2017)
Rhinoviruses are exclusive respiratory pathogens and the etiological agents of the common cold. These viruses are increasingly reported to cause exacerbations of asthma and chronic obstructive pulmonary disease (COPD). Here, we review the role of rhinovirus infections in the pathogenesis of asthma and COPD and we discuss the current and potential future treatments. We propose that, in order to prevent exacerbations, the design of novel therapeutics should focus on directly acting antivirals but also include the design of drugs that simultaneously inhibit viral replication and alleviate symptoms of asthma and COPD.